Skeletal Muscle Plasticity in Health and Disease From Genes to Whole Muscle - Bottinelli, Roberto; Reggiani, Carlo; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2006)
The ability of striated muscle tissue to adapt to changes in activity or in working conditions is extremely high. In some ways it is comparable to the ability of the brain to learn. The interest in muscle adaptation is increasing in relation to the idea that physical fitness helps in the prevention of disease, may counteract the loss of physical performance and generally improves wellbeing. Plasticity is the word used since the late 1970’s to indicate collectively all the processes and mechanisms which form the background of muscle adaptation. This book aims to provide a systematic updating of the available knowledge on molecular and cellular mechanisms, as well as on changes at whole muscle level. The book means to be a guide and a help for people who enter the field as PhD or medical students, but is also a tool for refreshing and updating knowledge for people already active in the field in basic sciences as well as in applied disciplines such as neurology, sports science and rehabilitation.
Skeletal muscle plasticity – history, facts and concepts -- Large Scale Gene Expression Profiles as Tools to Study Skeletal Muscle Adaptation -- Striated Muscle Plasticity: Regulation of the Myosin Heavy Chain Genes -- Signaling Pathways Controlling Muscle Fiber Size and Type In Response To Nerve Activity -- Activity Dependent Control of the Transcriptional regulators NFAT and HDAC in adult skeletal muscle fibres -- The Regulation of Satellite Cell Function in Skeletal Muscle Regeneration and Plasticity -- Plasticity of Excitation-Contraction Coupling in Skeletal Muscle -- Muscle Plasticity and Variations in Myofibrillar Protein Composition of Mammalian Muscle Fibers -- Muscle Architecture and Adaptations to Functional Requirements -- Responses and Adaptations of skeletal muscle to hormones and drugs -- Skeletal Muscle Adaptations to Disease States.
Keywords: Human physiology; Neurosciences; Cell biology; Developmental biology; Human Physiology; Neurosciences; Cell Biology; Developmental Biology